Industrially weavable metal/cotton yarn air electrodes for highly flexible and stable wire-shaped Li–O2 batteries. Issue 7 (27th January 2017) - Lin, Xiujing; Kang, Qi; Zhang, Ziqiang; Liu, Ruiqing; Li, Yi; Huang, Zhendong; Feng, Xiaomiao; Ma, Yanwen; Huang, Wei
Abstract : Flexible freestanding cathodes for Li–O2 batteries were fabricated massively by dyeing industrially weavable metal/cotton yarns with an active material ink. Abstract : Li–O2 batteries feature extremely high energy density, making their wire-shaped devices a promising candidate for wearable energy-storage application. However, it is a major challenge to explore industrially feasible electrodes for this type of linear batteries. Herein, for the first time, we have demonstrated an effective strategy to fabricate a feasible electrode on a large scale by dyeing industrially weavable and highly conductive metal/cotton yarns with the active material ink, RuO2 -coated nitrogen-doped carbon nanotube (CNT). The obtained wire-shaped Li–O2 battery exhibits a high discharge capacity of 1981 mA h gcarbon −1 at a current density of 320 mA gcarbon −1 and could stably work beyond 100 cycles (more than 600 hours) without obvious degradation, even under bending conditions. The new freestanding type electrode will represent a critical step towards the production and practical application of flexible Li–O2 batteries.